Beta-lactamases of enterobacteria: general characteristics, mechanisms and regional features of distribution. - Peretyatko, Olena; Yagniuk, Yuliia; Sklyar, Nadiya; Bolshakova, Galina; Holodna, Tetyana (Annals of Mechnikov’s Institute, 2022)
The problem of the formation and spread of resistance to β-lactam antibiotics in clinically significant types of microorganisms is extremely important, since β-lactams traditionally form the basis of the treatment of bacterial infections. Special attention of antibiotic resistance researchers is directed to the microorganisms of the Enterobacteriaceae family, namely, to pathogens such as Enterobacter spp., Citrobacter spp., Proteus spp., K. pneumoniae, E. coli, which are capable of producing a wide range of β-lactamases. Since the discovery of the first beta-lactamase in the 1960s, these enzymes have evolved, and today several hundred types of beta-lactamases have been discovered, but new varieties of them are constantly emerging and the dominant groups of these enzymes are changing. It has been discovered that some members of the Enterobacteriaceae family (Enterobacter spp., Citrobacter freundii, Morganella morganii, Serratia marcescens, Providencia spp.) have the ability to produce chromosomal cephalosporinases characterized by high affinity to 3rd generation cephalosporins. However, enterobacteria (Escherichia coli, Salmonella spp., Shigella spp., Klebsiella spp., Enterobacter spp., etc.) most often contain beta-lactamases of the TEM and SHV genetic groups, which are associated with plasmids and are responsible for the formation of resistance to penicillins and early cephalosporins, as well as the STX-M group responsible for resistance to broad-spectrum cephalosporins and monobactams. According to a number of researchers, the main groups of the β-lactamase family, represented by plasmid-mediated narrow-spectrum (NSBL) and extended-spectrum (ESBL) beta-lactamases, as well as AmpC cephalosporinases and carbapenemases, are spread throughout the world, however, predominance of specific beta-lactamases in certain geographical regions is observed. For example, while CTX-M enzymes are spread in all regions, serine carbapenemases are most often found in China, in the countries of North and South America and the Mediterranean, and metallo-betalactamases - in the Indonesian region and in the countries of Eastern Europe. In the countries of the Baltic region, the leading mechanism of resistance of enterobacteria to cephalosporins is the prevalence of extended-spectrum beta-lactamases (ESBLs) of the CTX-M class. Similar patterns of beta-lactamase genes distribution among clinical strains of enterobacteria were found in Spain, where the share of strains carrying the blaCTX-M gene was 93,3%. Significant spread of clinical strains of enterobacteria with resistance to beta-lactam antibiotics, especially ESBL-producing strains, necessitates constant monitoring of beta-lactam resistance and investigation of regional features of its distribution. Key words: Enterobacteriaceae family, Еnterobacteria, antibiotic resistance, formation mechanisms, beta-lactamases.